The spiralling swallow : a sociological auto-ethnography of "eating disorders(s)" and "recovery" - O'Farrell, Bríd (Trinity College (Dublin, Ireland). Department of Sociology, 2008)
This thesis is a sociological auto-ethnography of "eating disorder(s)" and "recovery".Using creative methodologies, I have created an intersubjective, poly-vocal account of bodies in encounter with medicine. I position this thesis as a counter-narrative and narrative of resistance to the hegemonic narratives circulated in contemporary Western cultures about health, healing and dys-order. Exploring the impact of dualistic medicalised cultures upon the lived experience of the body, I have posed questions about and offered reflections upon "ontology" ("ways of being") and "epistemology" ("ways of knowing"). In doing so I have contributed to sociologies theories of "eating disorder(s)" and offered reflections and theory on "recovery" when sociology seems, apart from a single study (Garrett, 1998), to have forgotten about this experience.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin